OP0086 Eular Recommendations for Women's Health and the Management of Family Planning, Assisted Reproduction, Pregnancy, and Menopause in Patients With Systemic Lupus Erythematosus and/or the Antiphospholipid Syndrome. (9th June 2015) - Andreoli, L.; Bertsias, G.; Agmon-Levin, N.; Brown, S.; Cervera, R.; Costedoat-Chalumeau, N.; Doria, A.; Fischer-Betz, R.; Forger, F.; Moraes-Fontes, M.; Khamashta, M.; King, J.; et al.
Abstract : Objectives: To develop recommendations for family planning, assisted reproduction, pregnancy, and menopause in women with SLE and/or APS. Methods: Research questions were compiled using a modified Delphi technique. A systematic PubMed search was performed using an array of index terms. Results: The preliminary set of recommendations are presented. SLE and/or APS patients planning a pregnancy should be counseled and managed after risk stratification by taking into consideration disease activity (active/flaring SLE, history of lupus nephritis or vascular/thrombotic events), serological profile (C3/C4, anti-dsDNA, anti-Ro/SSA, anti-La/SSB and antiphospholipid antibodies [aPL]), hypertension, and use of drugs (with emphasis on hydroxychloroquine (HCQ) and antiplatelet/anticoagulant therapy). SLE and/or APS women can be candidates for contraceptive measures based on their disease activity and thrombotic risk. Fertility preservation methods, especially GnRH analogues, should be considered prior to the use of alkylating agents. Assisted reproduction techniques seem to have comparable efficacy as in the general population, and can be safely used in patients with stable/inactive disease; patients with positive aPL/APS should receive appropriate anticoagulation and/or low dose aspirin. Disease activity, serological markers, and renal function parameters are useful to monitor for obstetrical adverse outcomes and disease flares during pregnancy. Fetal monitoring is similar to high-risk pregnancies including Doppler ultrasonography, particularly after 24-28 weeks of gestation to screen for placental insufficiency; fetal echocardiography is indicated for suspected fetal dysrhythmia, especially in patients with positive anti-Ro and/or anti-La. HCQ, glucocorticoids (oral/intravenous pulse), azathioprine, cyclosporine-A, tacrolimus and intravenous immunoglobulin can be used to prevent or manage SLE flares during pregnancy. If stable/inactive disease and negative aPL, hormonal replacement therapy can be used for severe vasomotor menopausal manifestations. Screening for malignancies is similar to the general population, with vigilance for cervical pre-malignant lesions if exposed to immunosuppressive drugs. Similar to the general population, HPV immunization should be considered in women with stable/inactive disease. Conclusions: Recommendations for women's health and pregnancy in SLE and/or APS patients were developed by evidence-based and expert consensus. Disclosure of Interest: None declared